Pengaruh Live Streaming dan Sales Promotion terhadap Impulse Buying yang Dimediasi oleh Consumer Shopping Motivation (Studi pada Gen Z Pengguna Shopee) - Safira, Afni Melati; Novie, Muhafidhah (SAFE-Network, 2024)
The aim of this study is to explain how live streaming and sales promotion affect the impulse buying mediated by consumer shopping motivation in Shopee users, Gen Z. The research uses quantitative methods. The data was collected through a structured questionnaire that was distributed to 97 selected people. Purposive sampling is a data collection method used. The study found that live streaming improves impulse buying, whereas sales promotion does not. Live streaming, sales promotions have a positive influence on impulses buying mediated by consumer shopping motivation.